Marketing Channels for Bali Cattle in Barangka District, Regency West Muna, Southeast Sulawesi - La Ode Arsad Sani; Natsir Sandiah; Ernia Ernia; Adrian Tawai; Deki Zulkarnain; Rina Astarika; La Ode Munadi (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2023)
Bali cattle marketing involves businesses to incur costs in every stage of the marketing channel. The research aims to analyze Bali cattle marketing channels and marketing margins in Barangka Subdistrict, West Muna Regency aug ust-October 2022. The research population is Bali cattle breeders and traders as many as 6 villages with the determination of the location determined stratified sampling based on the lowest, medium, high cow population with the selection of respondents purposive sampling. The results showed that Bali cattle marketing channels have 5 types, namely, (1) village-level producer-trader breeders-sub-district level traders-end-island-consumer collector traders, (2) village-level producer-trader breeders-end-island-consumer traders, (3)producer-trader breeders inter-sub-district-end-island-consumer traders, (4) end-consumer producer-merchants, (5) end-producer-consumer breeders. The largest Bali cattle marketing margin from producer breeders to retailers reached Rp. 2.620,489 per head and the smallest margin of livestock sales from producer breeders to village-level collectors was Rp. 1.035,823 per head.